AHL AL-KITĀB THROUGH THE INTERPRETATION OF THE TARTĪB NUZŪLĪ IZZAT DARWAZAH - Hamka Hasan (ILMU USHULUDDIN, 2022)
This article aims to describe the exclusiveness of the interpretation of the tartīb nuzūli model (an interpretation written based on the sūrah order) by Izzat Darwazah in his interpretation, Tafsīr al-Ḥadis. This article found that some ahl al-kitāb is disbelievers (kāfīr), while others are muʾmin. The term ahl al-kitāb is not only used by Jews and Christians but as Majūsī, Ṣābiʾīn, and others also receive books from Allah they also can be categorized as ahl al-kitāb. This article used a thematic interpretation method by collecting verses talking about ahl al-kitāb, and the discussion was carried out using a content analysis approach. We compared Tafsir al-Ḥadith written by Izzat Darwazah and other interpretation works. We concluded that not all ahl al-kitāb have similar attitudes to Prophet Muhammad and Muslims. Based on the Quran revelation order, as the basis of Sūrah’s order in writing this interpretation, Izzat Darwazah explained that the Quran describes the ahl al-kitāb in Mecca as softer than those in Madinah. Ahl al-kitāb in Mecca admitted the existence of Muhammad as the Prophet and Apostle and accepted the truth of his treatise, The Quran. Even they left their old faith and moved to Islam. Then, marriage and food exchange between Muslims and non-Muslims were allowed by the Quran as a big step in the road map of tolerance between Islam and other religions.